Zoom, Zoom, Baby! Assessing Mother-Infant Interaction During the Still Face Paradigm and Infant Language Development via a Virtual Visit Procedure - McElwain, Nancy L.; Hu, Yannan; Li, Xiaomei; Fisher, Meghan C.; Baldwin, Jenny C.; Bodway, Jordan M. (Frontiers in Psychology, 2022)
The COVID-19 pandemic has necessitated innovations in data collection protocols, including use of virtual or remote visits. Although developmental scientists used virtual visits prior to COVID-19, validation of virtual assessments of infant socioemotional and language development are lacking. We aimed to fill this gap by validating a virtual visit protocol that assesses mother and infant behavior during the Still Face Paradigm (SFP) and infant receptive and expressive communication using the Bayley-III Screening Test. Validation was accomplished through comparisons of data (i.e., proportions of missing data for a given task; observed infant and maternal behaviors) collected during in-person laboratory visits and virtual visits conducted via Zoom. Of the 119 mother-infant dyads who participated, 73 participated in lab visits only, 13 participated in virtual visits only, and 33 dyads participated in a combination of lab and virtual visits across four time points (3, 6, 9 and 12 months). Maternal perspectives of, and preferences for, virtual visits were also assessed. Proportions of missing data were higher during virtual visits, particularly for assessments of infant receptive communication. Nonetheless, comparisons of virtual and laboratory visits within a given time point (3, 6, or 9 months) indicated that mothers and infants showed similar proportions of facial expressions, vocalizations and directions of gaze during the SFP and infants showed similar and expected patterns of behavioral change across SFP episodes. Infants also demonstrated comparable expressive and receptive communicative abilities across virtual and laboratory assessments. Maternal reports of ease and preference for virtual visits varied by infant age, with mothers of 12-month-old infants reporting, on average, less ease of virtual visits and a preference for in-person visits. Results are discussed in terms of feasibility and validity of virtual visits for assessing infant socioemotional and language development, and broader advantages and disadvantages of virtual visits are also considered.